Effect of X-ray radiation on the pharmacokinetics of apatinib in vivo in rats - Dong, Shi-Qi; Yang, Fan; Zhang, Dong-Xu; Wang, Ling-Mei; Liu, Jian-Feng; Zhang, Ai-Jie; Fan, Hui-Rong (Frontiers in Pharmacology, 2022)
Purpose: The "radiation-pharmacokinetic"("RT-PK") phenomenon refers to the fact that radiation can significantly alter the pharmacokinetic behavior of a drug. At present, it is not clear whether there is a "RT-PK" phenomenon of apatinib in concurrent chemoradiotherapy. In this study, a rat irradiation model was used to study the effects of X-ray radiation on the absorption, tissue distribution and excretion of apatinib. Method: The healthy SD rats were randomly divided into control and radiation groups, and the radiation group was given an appropriate dose of abdominal X-ray radiation, both groups were given 45 mg/kg of apatinib solution by gavage after 24 hours of recovery. A quantitative LC-MS/MS method was developed to determine the concentration of apatinib to compare the differences between the control and radiation groups, and thus to investigate the modulating effect of radiation on the pharmacokinetics of apatinib in rats. Result: After abdominal X-ray irradiation, the area under the curve (AUC) of apatinib in rat plasma decreased by 33.8% and 76.3% at 0.5 Gy and 2 Gy, respectively. Clearance (CL) and volume of distribution (Vd) were significantly increased and positively correlated with radiation dose. X-ray radiation significantly reduced the concentration of apatinib in liver and small intestinal, and there was no tissue accumulation. In excretion studies, we found that X-ray radiation reduced the cumulative excretion of apatinib in feces and urine by 11.24% and 86.17%, respectively. Conclusion: Abdominal X-ray radiation decreased the plasma exposure, tissue distribution and excretion of apatinib in rats, suggesting a "RT-PK" phenomenon of apatinib, and we speculate that this "RT-PK" phenomenon is closely related to the changes of metabolic enzymes in vivo. In clinical practice, when apatinib is combined with radiotherapy, attention should be paid to adjusting the dose of apatinib and optimizing the treatment plan to alleviate the adverse effects of the "RT-PK" phenomenon.